Pure economic loss from a comparative perspective - Von Frentz,WFR (Centre for Law and Society, 2023)
English law originally did not provide an action in cases where pure economic loss was caused negligently. From the Middle Ages (i.e. from more or less the 13th century), when there arose a remedy called 'trespass', which was applicable only in cases of direct forcible injury,